Deteksi penyakit paru obstruktif kronis dengan peak flow metric pada masyarakat di Kelurahan Sukamaju Palembang - Fathurrachman, Alif; Indira, Dwi; Andriani, Linda; Pasaribu, Rouly; Sudarto, Sudarto; Rasyid, Ahmad; Ahmad, Zen (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2024)
. Chronic obstructive pulmonary disease (COPD) is a preventable and treatable lung disease characterized by persistent and often progressive respiratory symptoms and airflow resistance. COPD is still the 3rd leading cause of death in the world. Risk factors such as smoking and continuous exposure to air pollution are the causes of COPD. In diagnosing COPD, in addition to a history of respiratory symptoms and physical examination, a spirometry examination is needed to assess lung function capacity. However, this examination is not always available in health care facilities. Peak flow metric, which is used to assess lung capacity at maximal expiration, can be a cheap and easy-to-implement alternative. Early detection of COPD with peak flow metric will be beneficial for the community to know their lung function capacity earlier, so that people pay more attention to their lung health. Therefore, early detection of airway obstruction disorders in the community is needed through this community service activity. About 200 participants were given counseling about COPD and COPD detection was carried out using a peak flow metric tool. Of the 200 participants, 38% were detected to have airway obstruction with peak flow metric results <80%. This will be the basis for the community to check themselves to the health facility for spirometry examination, and increase public awareness to maintain lung health.